Millennial and Generation Z Online Purchasing Decisions on Indonesian Marketplace - Simamora, Virgo; Islami, Paras (Journal Research of Social Science, Economics, and Management, 2023)
The COVID-19 epidemic, as well as advancements in information technology, have both led to a shift in consumer behavior, with consumers increasingly preferring to purchase things online. This study is an explanatory study that aims to evaluate the impact of e-customer reviews, e-customer ratings, and e-payment on the online purchase decisions of Millennials and Generation Z in Indonesian marketplaces. The populations studied in this research include the Millennial Generation and Generation Z, both of which purchase products from Indonesian marketplaces in unknown, large numbers. Purposive sampling was employed in this investigation to gather 420 samples that fulfilled the specific criteria used in this study. This study employed a questionnaire to collect data, which was emailed using Google Forms and distributed between December 8, 2022, and January 16, 2023. According to the findings of this research, e-customer reviews have no impact on online purchasing decisions. In contrast, this study shows that e-customer ratings have an impact on online purchasing decisions. Finally, this research discovered that e-payment affected online purchasing decisions. The findings of this study are crucial because they provide insight into the preferences and attitudes of Generation Z and Millennials about e-customer reviews, e-customer ratings, and e-payment systems.